The importance of early immunotherapy in 103 patients with faciobrachial dystonic seizures - Thompson, J; Bi, M; Murchison, A; Makuch, M; Bien, C; Chu, K; Farooque, P; Gelfand, J; Geschwind, M; Hirsch, L; Somerville, E; Lang, B; et al. (Oxford University Press, 2017)
Faciobrachial dystonic seizures (FBDS) and limbic encephalitis closely associate with LGI1- antibodies. Here, we describe 103 consecutive patients with FBDS and LGI1-antibodies to understand clinical, therapeutic and serological differences between those with and without cognitive impairment (CI), and to determine whether cessation of FBDS can prevent CI. The 22/103 patients without CI typically had normal brain imaging, EEGs, sodium levels (p<0·0001) and almost exclusive IgG4 LGI1-antibodies, compared to the frequent IgG1- antibodies in patients with CI (p=0.009). Overall, cessation of FBDS with antiepileptic-drugs alone occurred in only 9/89 (10%) patients. In contrast, 30 days after immunotherapy initiation, 51% had cessation of FBDS (p<0·0001); an effect which was more rapid in those without CI (p=0.038). Moreover, every week of delayed immunotherapy conferred a 5% relative reduction in the probability of FBDS cessation. A shorter time to immunotherapy (p=0·031) and absence of CI (p=0·0014) predicted reduced disability at 24-months. Furthermore, of 80 patients with FBDS as their initial feature, 56% developed CI after 90 days of active FBDS. Only one patient developed CI after cessation of FBDS (p<0·0001). FBDS show a striking time-dependent response to immunotherapy, which appears to prevent development of CI, maybe via inhibiting complement-mediated neuronal destruction.